PENINGKATAN SEMANGAT KERJA KARYAWAN GUNA MENINGKATKAN PRODUKTIVITAS PADA PT. ANGKASA PURA LOGISTIC CABANG MAKASSAR - Guntur Suryo Putro (Jurnal Bisnis dan Kewirausahaan, 2016)
This study aims to determine the effect of employee morale How the productivity of employees at PT. Angkasa Pura Logistic Branch Makassar, the study was conducted during two months at PT. Angkasa Pura Logistic Makassar. The method used is Validity and Reliability. From the results of this study to test the validity (validity) and reliability testing (keterhandalan) of the items on all the variables, shows that there are validity and reliability. Because of the correlation coefficient values ​​that qualify valid and reliable at the critical value. As such items are used as a gauge for each variable in this study is used as a measuring tool worthy of study. The results of this study also showed that knowledge and understanding of the spirit of the work is an effective tool to determine the wishes of the employees themselves. Individual needs (X1), expectations of the individual (X2), fair treatment (X3) and clarity of purpose (X4) has a very important role for employees in the company.